2018
DOI: 10.1097/olq.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing and Macrolide Resistance of Syphilis Cases in Manitoba, Canada, From 2012 to 2016

Abstract: The finding of an increase in genetic diversity in the strains in this study and an increase in macrolide resistance compared with previous Canadian reports highlighted the need for continued surveillance including strain characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Our findings are in agreement with those reported by Casal et al [ 31 ], i.e., there was an association between PCR and tests for IgM. In addition, a better correlation between PCR and treponemal test vs. non-treponemal VDRL was reported by Shuel et al [ 32 ]. PCR positivity of whole blood samples appears to correlate with the early stages of syphilis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with those reported by Casal et al [ 31 ], i.e., there was an association between PCR and tests for IgM. In addition, a better correlation between PCR and treponemal test vs. non-treponemal VDRL was reported by Shuel et al [ 32 ]. PCR positivity of whole blood samples appears to correlate with the early stages of syphilis.…”
Section: Discussionsupporting
confidence: 93%
“…identification of syphilis. In fact, as shown in this and other studies [31,32], PCR positivity has been found to be positively associated with the results of the treponemal serological test. The group of RPR-negative and treponemal test-positive samples could, at least in part, represent samples from patients with a previous syphilis infection, especially in PCR negative samples taken from patients with an undetermined stage (n = 68).…”
Section: Plos Onesupporting
confidence: 84%
“…The second most common strains in this study were type 14d/g (also SS14-like clade), which were only found in samples from MSM, and were the second most prevalent type found in MSM samples. Type 14d/g strains were also previously reported to be the dominant strain type in the United States, France, Australia, Canada, and Italy (6,11,12,16,17). A strong link has been reported between type 14d/g strains and macrolide resistance (6,11,12,16,17).…”
Section: Discussionmentioning
confidence: 88%
“…Type 14d/g strains were also previously reported to be the dominant strain type in the United States, France, Australia, Canada, and Italy (6,11,12,16,17). A strong link has been reported between type 14d/g strains and macrolide resistance (6,11,12,16,17).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation